Penal Orders and the Role of Prosecutors in Switzerland - Enescu, Raluca (Journal of Legal Studies, 2020)
Minor infractions represent the majority of criminal cases. Simplified or summary procedures have addressed their increasing number in order to unburden the courts. Because of reduced requirements for the case to be adjudicated, this procedural economy comes usually to the cost of the defendant. Penal orders represent the most successful form of fast track procedure in which the public prosecutor plays a predominant role. After a police report and sometimes a short investigation, penal orders are issued and notified to the defendant. If they are not objected, their judgment equals the decision of a court. In other words, penal orders rely on the tacit agreement of the defendant. This contribution presents the risks of penal orders to produce wrongful convictions and proposes a set of recommendations that could improve the current situation. A combination of legal sources and empirical studies shed light on the delicate balance between the efficiency of justice and the defendant’s rights.